Expectations and Realities of Knowledge Management: Experiences from Higher Education in Developing Countries - Paudel, Krishna Prasad (Education and Development, 2019)
The aim of this paper is to view the theoretical and practical aspects of knowledge management in the higher education of developing countries of Asia and Africa. It also emphasizes the usage and importance of Knowledge Management (KM) in developing countries. This paper argues that the use of KM is growing day by day in higher education institution after the development of information technology (IT), and information and communication technology (ICT). KM is highlighted in the developing countries along with the enablers of KM such as technology, leadership, culture and environment. Consequently, development of KM is not going ahead as intended in such countries. The aim of this paper is to explore the status and impact of KM in higher education institutions (HEIs) of developing countries. In this era, the usage of KM is increasing day by day in business sectors and educational institutions as well. This paper aims to elaborate the expectations of KM in higher education institutes of developing countries.